Application of SILAC labeling to primary bone marrow-derived dendritic cells reveals extensive GM-CSF-dependent arginine metabolism - Fabrik, Ivo; Link, Marek; Härtlova, Anetta; Dankova, Vera; Rehulka, Pavel; Stulik, Jiri (Journal of proteome research, 2014)
Although dendritic cells (DCs) control the priming of the adaptive immunity response, a comprehensive description of their behavior at the protein level is missing. The introduction of the quantitative proteomic technique of metabolic labeling (SILAC) into the field of DC research would therefore be highly beneficial. To achieve this, we applied SILAC labeling to primary bone marow-derived DCs (BMDCs). These cells combine both biological relevance and experimental feasibility, as their in vitro generation permits the use of (13)C/(15)N-labeled amino acids. Interestingly, BMDCs appear to exhibit a very active arginine metabolism. Using standard cultivation conditions, ∼20% of all protein-incorporated proline was a byproduct of heavy arginine degradation. In addition, the dissipation of (15)N from labeled arginine to the whole proteome was observed. The latter decreased the mass accuracy in MS and affected the natural isotopic distribution of peptides. SILAC-connected metabolic issues were shown to be enhanced by GM-CSF, which is used for the differentiation of DC progenitors. Modifications of the cultivation procedure suppressed the arginine-related effects, yielding cells with a proteome labeling efficiency of ≥90%. Importantly, BMDCs generated according to the new cultivation protocol preserved their resemblance to inflammatory DCs in vivo, as evidenced by their response to LPS treatment.
Keywords: Molecular Sequence Data; kultivované buňky; sekvence aminokyselin; myši inbrední C57BL; Proline; Arginine; Chromatography, High Pressure Liquid; Mice; buňky kostní dřeně; vysokoúčinná kapalinová chromatografie; Dendritic Cells; Cells, Cultured; dendritické buňky; ženské pohlaví; Proteome; zvířata; prolin; Amino Acid Sequence; Bone Marrow Cells; Tandem Mass Spectrometry; myši; tandemová hmotnostní spektrometrie; arginin; molekulární sekvence - údaje; proteom; Female; faktor stimulující granulocyto-makrofágové kolonie; Granulocyte-Macrophage Colony-Stimulating Factor; Mice, Inbred C57BL; Animals